Trade Dependency, Bargaining and External Debt. (IMF Working Papers; Working Paper ;, 1988)
This paper analyzes the factors determining the payment on outstanding debt in the presence of partial defaults, and the feasibility of renewed investment. We show that a higher relative size of sectors with lower substitutability between domestic and foreign products will increase the resource transfer ceiling. Even with a partial default, investment in highly trade dependent sectors with high productivity may be warranted. This investment can be implemented by a marginal relief of the present debt service, in exchange for investment in the proper sector. A way to partially overcome some of the monitoring problems associated with renewed investment is through direct investment.